Analisis Efektifitas MBBR Dengan Aerasi Intermitten Dalam Menurunkan COD Dan NH3-N Pada Air Limbah RPH - Akhdan Praditya, Fawwaz; Raden Kokoh Haryo Putro; Muhammad Abdus Salam Jawwad (Jurnal Serambi Engineering, 2026)
Slaughterhouse wastewater contains high levels of organic matter and nitrogen, which can potentially pollute the environment if not properly treated. This study aims to analyze the effectiveness of the Moving Bed Biofilm Reactor (MBBR) system with intermittent aeration using pumice stone media in reducing Chemical Oxygen Demand (COD) and ammonia (NH₃-N) concentrations. The tested variables included media filling ratios (25%, 35%, and 45%) and hydraulic retention times (4, 6, and 8 hours) with balanced oxic–anoxic cycles. The results showed that increasing the media ratio and retention time significantly improved pollutant removal efficiency. The best performance was achieved with 45% media and an 8-hour retention time, resulting in COD and NH₃-N removal efficiencies of 87% and 82.8%, respectively. The pumice stone media effectively supported biofilm growth, which played a key role in the nitrification–denitrification processes. The intermittent MBBR technology with pumice media proved to be efficient, economical, and environmentally friendly for the treatment of slaughterhouse wastewater.